EXPRESSIVE ACTS OF CHARACTERS’ UTTERANCES IN THE AFTERMATH MOVIE - Hendra, Hendra; Ambalegin, Ambalegin (BASIS (Bahasa dan Sastra Inggris), 2023)
The researchers conducted the descriptive qualitative research to analyze the expressive acts types. This research used The Aftermath 2019 movie as the data source and data were utterances that characters produced to show their emotions to the hearers. The researchers took the data by using observational method and note-taking. The researchers did not appear in the movie and data were collected by also writing down. In analyzing data, pragmatic identity method and pragmatic competence- in equalizing were used. It was analyzed with the theory of expressive acts by Searle and Vanderveken (1985). The result showed the characters said all expressive acts types. There were 59 data found in the utterances. One data of congratulate, 14 data of apologize, one data of welcome, 15 data of thank, 14 data of greet, seven data of complain, and seven data of compliment. Based on the result, thank was dominant because the characters commonly used this type to show their feelings. The characters frequently expressed gratitude because the speakers got good benefits from the listeners